Underground Radio Propagation on Frequency Band 97 Mhz â€“ 130 Mhz - Suherman, S; Hanafiah Rambe, Ali; Widodo Tanjung, Agustiar (International Journal of Engineering and Technology, 2018)
Radio communications do not work only in the air and underwater, but also underground. Some applications such as mining and earthquake detection require underground radio devices. This paper reports an assessment of underground radio characteristics for frequency band 97 MHz to 130 MHz. The assessments were performed through an experimental propagation measurement and a mathematical prediction. Both assessments then are compared by using the normalized graph to predict propagation characteristics so that correct link budget for future application can be assisted. The mathematic analysis and measurement results still produce huge errors; achieving 50.33% for frequency 130.762 MHz, 17.58% for 109.818 MHz and 13.38% for 97.335 MHz. Error can be minimized when the ground permittivity is more preciseÂ Â